2018
DOI: 10.1029/2018jc013992
|View full text |Cite
|
Sign up to set email alerts
|

A Coupled Ocean Physics‐Biology Modeling Study on Tropical Instability Wave‐Induced Chlorophyll Impacts in the Pacific

Abstract: Tropical instability waves (TIWs) play an important role in modulating the physical variability (e.g., sea surface temperature [SST] and heat flux) and biological activity (e.g., phytoplankton and chlorophyll (Chl)) in the eastern tropical Pacific. The impacts of TIW‐induced Chl perturbations (ChlTIW) are examined using a coupled ocean physics‐biology model in the tropical Pacific. TIW‐scale biological and physical perturbations are extracted using a zonal high‐passed filter. The TIW‐induced perturbations of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 69 publications
2
10
0
Order By: Relevance
“…Compared with FILT (Figure S8), the SST is cooling by 0.1–0.2 °C in CTRL during La Niña event, demonstrating the Chl TIW effect induces a cooling during La Niña event. This result is also consistent with previous ocean general circulation model study (Tian et al, ).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Compared with FILT (Figure S8), the SST is cooling by 0.1–0.2 °C in CTRL during La Niña event, demonstrating the Chl TIW effect induces a cooling during La Niña event. This result is also consistent with previous ocean general circulation model study (Tian et al, ).…”
Section: Resultssupporting
confidence: 94%
“…Additionally, the HCM can well simulate coherent structure of SST and Chl at TIW scale (Figures a–d); that is, high Chl concentration corresponds to cold SST phase, whereas low Chl concentration corresponds to warm SST phase (Figures c–d). The amplitude of Chl TIW is 0.05–0.1 mg/m 3 , which is in good agreement with estimates from observations (Tian et al, ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The model used in this study is a coupled ocean physics‐biogeochemistry model (Tian et al, ; Wang et al, ; Wang, Le Borgne, et al, ; Zhang et al, ), which consists of an ocean general circulation model (OGCM) and a biogeochemistry model. It is also the ocean component of the hybrid‐coupled model for atmosphere‐ocean and biogeochemistry (HCM‐AOPB), which is employed in ZH19.…”
Section: Model Data Used and Experimentsmentioning
confidence: 99%
“…Previous studies documented basic performances of the coupled ocean physics‐biogeochemistry model, which shown that the model could well simulate mean state, seasonal cycle, and interannual variability in the physical and biological fields (Tian et al, ; Wang et al, , ; Zhang et al, ). Figure shows the response of chlorophyll to ENSO for the observations and model forced by observed and reanalysis atmospheric forcing.…”
Section: Overview Of the Model Simulationsmentioning
confidence: 99%